Spatial Structure and Decadal Spatiotemporal Distribution of the Anchoveta ( Engraulis ringens ) in the Marine Ecosystem of the Peruvian Current Between 1985 and 2024 - Pedro Ramiro Castillo; Han Xu; Gustavo Cuadros; Daniel Grados; Carlos Valdez; Rodolfo Cornejo; Marissela Pozada‐Herrera (Fisheries Oceanography, 2025)
This paper presents the spatial structure with geostatistical analysis and decadal spatiotemporal distribution of anchoveta according to the Pacific Decadal Oscillation index, its implications for the anomalous events of the oceanographic conditions of the Northern Region of the Humboldt Current System (NRHCS), and areas of high anchoveta abundance found in the analyzed period. The acoustic data came from the Hydroacoustic Pelagic Resources Assessment Surveys carried on by the Instituto del Mar del Peru (IMARPE), and the oceanographic data came from satellite images of sea surface thermal anomalies (SSTA) between 1985 and 2024. The results showed that anchoveta has had a positive linear trend, with a high positive spatial autocorrelation and a structure spatially dependent on invironmental conditions in space and time. In the cold decadal periods, anchoveta were found a little far from the coast, distributed in high concentrations mainly in the north‐central region, while in the warm decadal periods, they were found close to the coast and with greater abundance towards the central zone; exceptional was in the warm period of 1985–1988, where anchoveta distribution was wide and generally dispersed. The trend in the warm decadal periods was negative, and in the decadal periods, it was positively influenced by El Niño events: 1997–1998 and 2015–2016, with a decrease in biomass recorded in 1998 and 2015. In the last cold period, 2017–2024, it was influenced by the warm year of 2023. Between 2000 and 2024, anchoveta biomass averaged 8.26 million tons, with an average biomass of 7.46 million tons for the north‐central region between 2004 and 2024.

Distribution and abundance of squat lobster (Pleuroncodes monodon) and its association with anchoveta in the coastal zone of the Peruvian Current (1998–2024) - Pedro Ramiro Castillo; Luis La Cruz; Carlos Valdez; Gustavo Cuadros; Ketty Ferrel; Marissela Pozada-Herrera; Rodolfo Cornejo; Aníbal Aliaga; Daniel Grados (Frontiers in Marine Science, 2025)
The squat lobster or munida ( Pleuroncodes monodon ) is one of the most abundant species in the coastal zone of the Peruvian Current. Due to its high incidence of occurrence and biomass, it has been monitored since 1998 by the Instituto del Mar del Perú (IMARPE) through the Hydroacoustic Assessment Surveys for Anchoveta and Other Pelagic Resources. In this study, 59 surveys conducted between 1998 and 2024 were analyzed to study the spatial distribution, abundance, and ecological relationship of munida with anchoveta ( Engraulis ringens ). The results showed that between 1998 and 2000, munida expanded its distribution northward along the Peruvian coast, while from 2001 onward its range remained relatively stable. A clear seasonal pattern was identified: during winter and spring, both the distribution area and inertia increased, and the species tended to occur farther from the coast, whereas in summer and autumn the distribution contracted, except during anomalous oceanographic events (e.g., warm or cold conditions). Vertically, munida generally inhabited the surface layer down to approximately 168 m, although during the 2015 -2016 El Niño event it was recorded as deep as 203 m. The average biomass throughout the study period was close to 2.04 million tons, with a maximum of 5.38 million tons recorded during survey 1703-04. Munida was also the species most closely associated with anchoveta, and when both occurred together, their interaction varied depending on the time of day, probably reflecting diel vertical migration and differential aggregation behaviors. These findings suggest that munida is a key component of the Peruvian Current ecosystem, whose variability is influenced both by seasonal cycles and by anomalous oceanographic conditions, and that its association with anchoveta may have implications for ecosystem functioning and fisheries management in the region.

Cross-canyon variability in zooplankton backscattering strength in a river-influenced upwelling area - Macarena Díaz-Astudillo; Manuel I. Castillo; Pedro A. Figueroa; Leonardo R. Castro; Ramiro Riquelme-Bugueño; Iván Pérez-Santos; Oscar Pizarro; Gonzalo S. Saldías (Ocean Science, 2025)
Zooplankton are a key component of food webs in upwelling systems. Their distribution is influenced not only by mesoscale and climate dynamics but also by topography and local currents. Submarine canyons that incise the continental shelf can act as conduits, transporting deep, nutrient-rich waters to shallower regions and promoting coastal biological productivity. Consequently, these canyons facilitate the advection and accumulation of zooplankton. We aimed to describe the spatio-temporal variability in zooplankton distribution (using net samples and acoustic data) and their association with local currents in a long, narrow submarine canyon located in the highly productive continental shelf off central Chile. The backscattering strength (Sv), a proxy for zooplankton biomass, was highly variable on both diurnal and spatial scales. Higher Sv and abundances were found at night, following the classic diel vertical migration pattern. Zooplankton were not uniformly distributed within the canyon. In the surface and mid-depth layers, the canyon walls accumulated more zooplankton than the center, particularly during the nighttime. Within the canyon, the currents were asymmetrical and frequently reversed direction. When the positive along-canyon current was stronger on the northern slope, Sv was also higher on that wall. This pattern was especially evident in the section closer to the canyon head. We show that the Biobio Canyon is a highly dynamic environment where oceanographic conditions can rapidly shift. Our findings suggest a feasible mechanism for zooplankton retention driven mainly by along-canyon flow asymmetry and vertical migrations.

Enhancing meaningful Indigenous leadership and collaboration in international environmental governance forums - Melanie Zurba; Sandie Suchet-Pearson; Ryan Bullock; Ameyali Ramos Castillo; Kevin Chang; Ricky Archer; Eli Enns; Pasang Dolma Sherpa; Ramiro Batzin; Osvaldo Munguia; Anastasia Papadopoulos; Bryanne Lamoureux; et al. (Environmental Science & Policy, 2024)

Cytotoxic and antiproliferative activity of thiazole derivatives of Ochraceolide A - Angel D. Herrera-España; Jenner Us-Martín; Carlos Quintal-Novelo; Gumersindo Mirón-López; Ramiro F. Quijano-Quiñones; David Cáceres-Castillo; Manlio Graniel-Sabido; Rosa E. Moo-Puc; Gonzalo J. Mena-Rejón (Natural Product Research, 2022)

Characteristics of anchoveta ( Engraulis ringens ) schools in the optimum zone and the physiological stress zone of its distribution between 2011 and 2021 - Pedro Ramiro Castillo; Cecilia Peña; Daniel Grados; Luis La Cruz; Carlos Valdez; Marissela Pozada‐Herrera; Rodolfo Cornejo (Fisheries Oceanography, 2022)
This study has considered anchoveta acoustic data from the Pelagic Resources Hydroacoustic Assessment Surveys carried out by the Peruvian Sea Institute (IMARPE) and free access satellite data (HYCOM and MODIS from the USA) of some oceanographic variables between the period 2011 and 2021, to know the oceanographic conditions, characteristics of schools and size structure in the optimum zone (OZ) and in the physiological stress zone (PSZ), of their total distribution. The OZ is determined by the extent of the Cold Coastal Waters (CCW), and the PSZ is determined by the mixing of waters, to the north by the CCW‐ESW (Equatorial Surface Waters) and to the west between the CCW‐SSW (Subtropical Surface Waters). The range of sea surface temperature and salinity in the PSZ (16.1–25.0°C and 34.65–35.29, respectively) was wider than in the OZ (14.5–24.0°C and 34.65–35.20, respectively), where a higher number of schools were recorded. Our analyses showed that the morphometric and energetic acoustic descriptors of anchoveta schools in the summer were higher during summers compared to springs. In terms of positional characteristics, the mean depth of the schools in the PSZ was slightly greater than in the OZ. The total size structure of anchoveta in the OZ consisted mainly of juvenile specimens (less than 12 cm total length) in the summer of 2011 and 2013–2014 and in the spring between 2014–2017 and 2021. In the PSZ, adult specimens (greater than 12 cm total length) predominated in summer between 2011–2013, 2015, 2018, and 2021 and in spring between 2011–2013, 2015, and between 2018–2021. However, specimens greater than 10 cm in total length were found in the PSZ. Knowledge of the location of this zone away from the coast will allow a high probability of anchoveta capture of adult specimens during fishing periods.

Synthesis, in vitro antigiardial activity, SAR analysis and docking study of substituted chalcones - David Cáceres-Castillo; Rubén M. Carballo; Ramiro Quijano-Quiñones; Gumersindo Mirón-López; Manlio Graniel-Sabido; Rosa E. Moo-Puc; Gonzalo J. Mena-Rejón (Medicinal Chemistry Research, 2020)

Assessing the viral content of uncultured picoeukaryotes in the global‐ocean by single cell genomics - Yaiza M. Castillo; Jean‐François Mangot; Luiz Felipe Benites; Ramiro Logares; Megumi Kuronishi; Hiroyuki Ogata; Olivier Jaillon; Ramon Massana; Marta Sebastián; Dolors Vaqué (Molecular Ecology, 2019)
Viruses are the most abundant biological entities on Earth and have fundamental ecological roles in controlling microbial communities. Yet, although their diversity is being increasingly explored, little is known about the extent of viral interactions with their protist hosts as most studies are limited to a few cultivated species. Here, we exploit the potential of single‐cell genomics to unveil viral associations in 65 individual cells of 11 essentially uncultured stramenopiles lineages sampled during the Tara Oceans expedition. We identified viral signals in 57% of the cells, covering nearly every lineage and with narrow host specificity signal. Only seven out of the 64 detected viruses displayed homologies to known viral sequences. A search for our viral sequences in global ocean metagenomes showed that they were preferentially found at the DCM and within the 0.2–3 µm size fraction. Some of the viral signals were widely distributed, while others geographically constrained. Among the viral signals we detected an endogenous mavirus virophage potentially integrated within the nuclear genome of two distant uncultured stramenopiles. Virophages have been previously reported as a cell's defence mechanism against other viruses, and may therefore play an important ecological role in regulating protist populations. Our results point to single‐cell genomics as a powerful tool to investigate viral associations in uncultured protists, suggesting a wide distribution of these relationships, and providing new insights into the global viral diversity.

Anchovy distribution off Peru in relation to abiotic parameters: A 32‐year time series from 1985 to 2017 - Ramiro Castillo; Luciano Dalla Rosa; Walter García Diaz; Lauro Madureira; Mariano Gutierrez; Luís Vásquez; Rolf Koppelmann (Fisheries Oceanography, 2019)
Oceanographic and hydroacoustic data were obtained by the Instituto del Mar del Peru ( IMARPE ) during 72 cruises off the Peruvian coast between 1985 and 2017 to determine the ranges of the abiotic parameters influencing the anchovy (anchoveta) distribution and to observe the effect of the 1997–1998 El Niño event. The hydroacoustic data show a high seasonal variability in anchoveta distribution related to differences of environmental parameters as well as changes in distribution after the very strong El Niño event in 1997–1998. Geostatistic variograms were used to describe the seasonal variability and generalized additive models ( GAM s) with a Tweedie distribution were applied to study the relationships between anchoveta and oceanographic parameters. The dependent variable was the value for anchoveta obtained from echosounder (nautical area scattering coefficient [ NASC ] of anchoveta) and the tested covariates were temperature, salinity, and dissolved oxygen at the sea surface; distance to the coast; year, latitude–longitude; and Oceanic Niño Index 1 + 2. The results show a high variability of anchoveta with seasonal differences in its distribution. Preferred abiotic conditions (temperature, salinity, oxygen) of anchoveta were 17.6–23.7°C, 32.30–35.14, and 5.9–8.7 ml/L in summer and 14.5–18.8°C, 34.81–35.12, and 5.2–6.3 ml/L in winter. The values in autumn and spring were intermediate and are considered as in transition. The anchoveta were detected at higher values after the 1997–1998 El Niño event, probably influenced by reduced standing stocks of congener fish species and by the Pacific decadal oscillation ( PDO ) or by a changes in climate.

Impact of grafting on sensory profile of tomato landraces in conventional and organic management systems - Joan Casals; Aurora Rull; Mauro Bernal; Ramiro González; Roser Romero del Castillo; Joan Simó (Horticulture, Environment, and Biotechnology, 2018)

Wetland plant species improve performance when inoculated with arbuscular mycorrhizal fungi: a meta-analysis of experimental pot studies - Thai Khan Ramírez-Viga; Ramiro Aguilar; Silvia Castillo-Argüero; Xavier Chiappa-Carrara; Patricia Guadarrama; José Ramos-Zapata (Mycorrhiza, 2018)

Native‐predator–invasive‐prey trophic interactions in Tierra del Fuego: the beginning of biological resistance? - Simón P. Castillo; Ramiro D. Crego; Jaime E. Jiménez; Ricardo Rozzi (Ecology, 2017)

Seasonality in marine ecosystems: Peruvian seabirds, anchovy, and oceanographic conditions - Giannina Passuni; Christophe Barbraud; Alexis Chaigneau; Hervé Demarcq; Jesus Ledesma; Arnaud Bertrand; Ramiro Castillo; Angel Perea; Julio Mori; Vincent A. Viblanc; Jose Torres‐Maita; Sophie Bertrand (Ecology, 2016)
In fluctuating environments, matching breeding timing to periods of high resource availability is crucial for the fitness of many vertebrate species, and may have major consequences on population health. Yet, our understanding of the proximate environmental cues driving seasonal breeding is limited. This is particularly the case in marine ecosystems, where key environmental factors and prey abundance and availability are seldom quantified. The Northern Humboldt Current System ( NHCS ) is a highly productive, low‐latitude ecosystem of moderate seasonality. In this ecosystem, three tropical seabird species (the Guanay Cormorant Phalacrocorax bougainvillii , the Peruvian Booby Sula variegata , and the Peruvian Pelican Pelecanus thagus ) live in sympatry and prey almost exclusively on anchovy, Engraulis ringens . From January 2003 to December 2012, we monitored 31 breeding sites along the Peruvian coast to investigate the breeding cycle of these species. We tested for relationships between breeding timing, oceanographic conditions, and prey availability using occupancy models. We found that all three seabird species exhibited seasonal breeding patterns, with marked interspecific differences. Whereas breeding mainly started during the austral winter/early spring and ended in summer/early fall, this pattern was stronger in boobies and pelicans than in cormorants. Breeding onset mainly occurred when upwelling was intense but ecosystem productivity was below its annual maxima, and when anchovy were less available and in poor physiological condition. Conversely, the abundance and availability of anchovy improved during chick rearing and peaked around the time of fledging. These results suggest that breeding timing is adjusted so that fledging may occur under optimal environmental conditions, rather than being constrained by nutritional requirements during egg laying. Adjusting breeding time so that fledglings meet optimal conditions at independence is unique compared with other upwelling ecosystems and could be explained by the relatively high abundances of anchovy occurring throughout the year in the NHCS .

Metagenomic 16S rDNA I llumina tags are a powerful alternative to amplicon sequencing to explore diversity and structure of microbial communities - Ramiro Logares; Shinichi Sunagawa; Guillem Salazar; Francisco M. Cornejo‐Castillo; Isabel Ferrera; Hugo Sarmento; Pascal Hingamp; Hiroyuki Ogata; Colomban de Vargas; Gipsi Lima‐Mendez; Jeroen Raes; Julie Poulain; et al. (Environmental Microbiology, 2014)
Summary Sequencing of 16S rDNA polymerase chain reaction ( PCR ) amplicons is the most common approach for investigating environmental prokaryotic diversity, despite the known biases introduced during PCR . Here we show that 16S rDNA fragments derived from Illumina‐sequenced environmental metagenomes ( mi tag s) are a powerful alternative to 16S rDNA amplicons for investigating the taxonomic diversity and structure of prokaryotic communities. As part of the T ara O ceans global expedition, marine plankton was sampled in three locations, resulting in 29 subsamples for which metagenomes were produced by shotgun Illumina sequencing (ca. 700 Gb). For comparative analyses, a subset of samples was also selected for R oche‐454 sequencing using both shotgun ( m454 tag s; 13 metagenomes, ca. 2.4 Gb) and 16S rDNA amplicon ( 454 tag s; ca. 0.075 Gb) approaches. Our results indicate that by overcoming PCR biases related to amplification and primer mismatch, mi tag s may provide more realistic estimates of community richness and evenness than amplicon 454 tag s. In addition, mi tag s can capture expected beta diversity patterns. Using mi tag s is now economically feasible given the dramatic reduction in high‐throughput sequencing costs, having the advantage of retrieving simultaneously both taxonomic ( B acteria, A rchaea and E ukarya) and functional information from the same microbial community.

Cardiac Tissue Injury Resistance During Myocardial Infarction at Adulthood by Developmental Exposure to Cadmium - Ramiro Zepeda; Paula Castillo; Daniel Sáez; Miguel N. Llanos; Ana M. Ronco (Cardiovascular Toxicology, 2012)

Field performance of artificial seed-derived sugarcane plants - Nadina Nieves; Yumaris Zambrano; Raúl Tapia; Mariela Cid; Danilo Pina; Ramiro Castillo (Plant Cell, Tissue and Organ Culture (PCTOC), 2003)

Biochemical characterization of embryogenic and non-embryogenic calluses of sugarcane - Nadina Neves; Magdalena Segura-Nieto; María A. Blanco; Margelys Sánchez; Alfredo González; Justo L. González; Ramiro Castillo (In Vitro Cellular & Developmental Biology - Plant, 2003)

Storage proteins in sugarcane: An interesting exception in monocots - Maria A. de los Blanco; Magdalena Segura-Nieto; Ramiro Castillo; Nadina Nieves (Plant Cell, Tissue and Organ Culture (PCTOC), 1999)

Protein changes associated with plant regeneration in embryogenic calli of sugarcane (Saccharum sp.). - María A. de los Blanco; Nadina Nieves; Margelys Sánchez; Carlos G. Borroto; Ramiro Castillo; Justo L. González; Maritza Escalona; Evelio Báez; Zulema Hernández (Plant Cell, Tissue and Organ Culture (PCTOC), 1997)